2020
DOI: 10.1155/2020/2473469
|View full text |Cite
|
Sign up to set email alerts
|

Level of Patient Satisfaction with Inpatient Services and Its Determinants: A Study of a Specialized Hospital in Ethiopia

Abstract: Background. The health care industry is undergoing a rapid transformation to meet the ever-increasing needs and demands of its patient population. Level of patients’ satisfaction is an important health outcome, which is regarded as a determinant measure for quality of care. This study was performed with the aim of assessing the level of patient satisfaction with inpatient services and its determinants in Black Lion Specialized Hospital, Addis Ababa, Ethiopia. Methods. A facility-based cross-sectional study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 34 publications
3
40
1
6
Order By: Relevance
“… 4 The possible reason for the difference could be the difference in the availability of essential resources, both human (staff number and skill to manage the referral), and physical (infrastructure, transport), and as well as communication and coordination of the referring and receiving health facilities. The overall satisfaction rate toward referral was consistent with studies conducted in other services such as inpatient service satisfaction 46.2%, 12 which is higher than studies done in the outpatient service satisfaction 27.8%. 13 But the result of this study is lower as studies done in the emergency service satisfaction 56%, 14 antenatal care service satisfaction 73.3%.…”
Section: Discussionsupporting
confidence: 85%
“… 4 The possible reason for the difference could be the difference in the availability of essential resources, both human (staff number and skill to manage the referral), and physical (infrastructure, transport), and as well as communication and coordination of the referring and receiving health facilities. The overall satisfaction rate toward referral was consistent with studies conducted in other services such as inpatient service satisfaction 46.2%, 12 which is higher than studies done in the outpatient service satisfaction 27.8%. 13 But the result of this study is lower as studies done in the emergency service satisfaction 56%, 14 antenatal care service satisfaction 73.3%.…”
Section: Discussionsupporting
confidence: 85%
“…In the literature it has been shown how drugs and medical equipment availability (13), availability of laboratory, radiology services and rooms for accommodation (19) can influence patients' satisfaction. On the other hand, there is evidence that parental satisfaction in provincial centers is higher than in national specialist centers, probably due to the lower severity of cases and less stressful working conditions (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The medical research ethics review board of one of the hospitals (an Academic Hospital) and of the Oromia Regional Health Bureau approved the study protocol. Considering the local cultural context (18), a verbal informed consent was obtained from all study participants (19)(20)(21). Parents were informed about the study objectives and data were collected anonymously.…”
Section: Ethical Issuesmentioning
confidence: 99%
“…Another national study from Karachi showed that almost 65% of the patients were satisfied in a multi-centered setting [9]. An Ethiopian study also demonstrated that 46% of the total patients were satisfied with the services they received [19]. Although, an investigation from Iran exhibited that 83% of their sample population was satisfied with the services provided at a tertiary care hospital [20].…”
Section: Discussionmentioning
confidence: 99%